1 to 1, 11,111 Covid sample testing; Decoding the testing matrix! - Nikam, Chaitali; Sengupta, Caesar; K, Kallathikumar; S, Krishnakumar; Ganesan, PraveenKumar (Asian Journal of Medical Sciences, 2021)
Almost 100 yrs. after the 1918 Spanish Flu Pandemic, world is witnessing “Covid-19”, another Pandemic of similar scale. Interesting, parallels are being drawn between these two pandemics –occurring a century apart; on their scale of spread, potential impact, global scare and attention, containment measures and even people are framing similar projections on possible course of the pandemic. While world was equally unprepared on many terms to safeguard itself from such a pandemic from SARS Cov-2 Virus, one scenario quite distinct from the previous pandemic scenario, is the current status of laboratories with advanced tools. Ground breaking genomic technologies such as NAAT (Nucleic acid Amplification technologies) or PCR (Polymerase Chain Reaction), which currently exist can be positioned as crucial weapons strategically for both community level operations and patient level care. We have the opportunity for cross learning from the experiences of the laboratories involved in Covid testing while informing our peers across policy, diagnostic and research domains, exciting the newcomers to join forces and educating all our associates who can be involved in supportive roles and the large numbers of innovators / supporters who can offer to improvise and strengthen on our current solutions.